Volunteer farmer-trainer motivations in East Africa: practical implications for enhancing farmer-to-farmer extension - Kiptot, Evelyne; Karuhanga, Monica; Franzel, Steven; Nzigamasabo, Paul Benjamin (Informa UK Limited, 2016)
Farmer-to-farmer extension (FFE) has received considerable interest in developing countries due to a decline in government extension services. There are, however, questions as to how FFE can be improved to enhance effectiveness and sustainability of the approach. One area that may hold the key is to understand volunteer farmer-trainer (VFT) motivations. Informal and formal interviews were held with VFTs in a smallholder dairy development project in Kenya, Uganda and Rwanda. Data were collected on the reasons why VFTs became trainers and why they continue to train. Findings of the study showed that VFTs were motivated by a combination of intrinsic and extrinsic factors. These factors are not static; they change over time. Gaining knowledge and skills as well as altruism were found to be the most important motivating factors for becoming trainers in the three countries. However, a few years after becoming trainers, income earned from selling inputs and specialized services associated with training was an important motivating factor to VFTs in Kenya. In Uganda gaining knowledge and skills remained the most important whereas in Rwanda, a new motivation, increased demand for training, was the most important reason for continuing to train. These findings point to the fact that the general reasons that motivate VFTs irrespective of context are similar; however, the importance attached to motivations is context specific. These motivations can provide insights into which incentives can be enhanced to improve effectiveness and sustainability of FFE.